2021
DOI: 10.3390/geriatrics6040107
|View full text |Cite
|
Sign up to set email alerts
|

Snoring Remediation with Oral Appliance Therapy Potentially Reverses Cognitive Impairment: An Intervention Controlled Pilot Study

Abstract: Respiration rate (RR) dynamics entrains brain neural networks. RR differences between mild cognitive impairment (MCI) and Alzheimer’s disease (AD) in response to oral appliance therapy (OAT) are unknown. This pilot study investigated if RR during stable sleep shows a relationship to pathological severity in subjects with MCI and AD who snore and if RR is influenced following stabilization of the upper airway using OAT. The study cohort was as follows: cognitively normal (CN; n = 14), MCI (n = 14) and AD (n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…These results complement the report by Edwards and colleagues, who found that oral appliances improved passive anatomical collapsibility and ventilation (Edwards et al, 2016). Enabling nasal breathing using the added mouth shield likely improved ventilation efficiency (Teschler et al, 1999), while both oral appliance plus mouth shield and oral appliance only reduced snoring (Rappai et al, 2003;Norrhem and Marklund, 2016;Schramm et al, 2021) and upper from baseline T1 −0.6 (−0.8 to 0.3) 2.5 (0.5 to 3.7) 0.003 T2 0.5 (−0.3 to 0.6) 3.5 (0.9 to 3.5) 0.017 T3 −0.3 (−0.8 to 0.3) 2.9 (−1.7 to −0.1) 0.019…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These results complement the report by Edwards and colleagues, who found that oral appliances improved passive anatomical collapsibility and ventilation (Edwards et al, 2016). Enabling nasal breathing using the added mouth shield likely improved ventilation efficiency (Teschler et al, 1999), while both oral appliance plus mouth shield and oral appliance only reduced snoring (Rappai et al, 2003;Norrhem and Marklund, 2016;Schramm et al, 2021) and upper from baseline T1 −0.6 (−0.8 to 0.3) 2.5 (0.5 to 3.7) 0.003 T2 0.5 (−0.3 to 0.6) 3.5 (0.9 to 3.5) 0.017 T3 −0.3 (−0.8 to 0.3) 2.9 (−1.7 to −0.1) 0.019…”
Section: Discussionsupporting
confidence: 84%
“…Studies using custom-fitted oral appliances (Byun et al, 2020;Schneiderman et al, 2021;Labarca et al, 2022) or temporary oral appliances (Schramm et al, 2021;Segù et al, 2021) confirm significant AHI or respiratory event index and snoring reduction, regardless of oral appliance brand or design. However, these investigations included heterogeneous OSA patients, making the interpretation of oral appliance efficacy among the OSA mouth breathing phenotype difficult.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations